A Literary Review on the Medicinal Use of Dhatura: A Well-known Folklore Poison W.S.R. Various Rasa Grantha - Monika Jashvantbhai Patel; Arati Abhay Shinde (Journal of Ayurveda)
Introduction:Dhatura is a well-known folklore medicinal herb having both toxic and therapeutic properties. It contains a number of toxic alkloids, including scopolamine, hyoscine, and atropine. After the proper Shodhana process, this poisonous plant exhibits great pharmacological potential as established in Ayurvedic texts. In this review article, an attempt has been made to compile the therapeutic use of dhatura critically, from about 8 rasa grantha. Dhatura has been found effective against more than 50 disease conditions. Studies reporting its antibacterial, antiasthmatic, hypoglycemic, anticancer, antioxidant, and antigout activity have also been included to prove the wide range of medicinal values of this plant.Objectives:To review the various rasa grantha for enlisting formulations having dhatura as an ingredient. (1) To segregate the formulations found disease wise for establishing therapeutic dominance of Dhatura. (2) To correlate its action found with the recent advances.Data Source:Total 8 rasa grantha: Rasa Ratna Samucchaya, Rasendra Sara Samgraha, Rasa Manjari, Rasendra Chintamani, Rasamritam, Rasa Tarangini, Rasatantra saar evum Siddha Prayoga Sangraha, and Rasa Kaam Dhenu have been referred for our purpose.Review Methods:Above mentioned rasa grantha were reviewed and formulations containing dhatura have been listed out.Result and Conclusion:After screening these 8 rasa grantha, a total 146 formulations have been found which have dhatura as an ingredient for both internal and external medication. Furthermore, the therapeutic dominance which we have found has been validated by comparing it with modern Studies and researches.